Epidermal Th22 and Tc17 Cells Form a Localized Disease Memory in Clinically Healed Psoriasis - Cheuk, Stanley (AAI, 2014)
Psoriasis is a common and chronic inflammatory skin disease in which T cells play a key role. Effective treatment heals the skin without scarring, but typically psoriasis recurs in previously affected areas. A pathogenic memory within the skin has been proposed, but the nature of such site-specific disease memory is unknown. Tissue-resident memory T (T(RM)) cells have been ascribed a role in immunity after resolved viral skin infections. Because of their localization in the epidermal compartment of the skin, T(RM) may contribute to tissue pathology during psoriasis. In this study, we investigated whether resolved psoriasis lesions contain T(RM) cells with the ability to maintain and potentially drive recurrent disease. Three common and effective therapies, narrowband-UVB treatment and long-term biologic treatment systemically inhibiting TNF-α or IL-12/23 signaling were studied. Epidermal T cells were highly activated in psoriasis and a high proportion of CD8 T cells expressed T(RM) markers. In resolved psoriasis, a population of cutaneous lymphocyte–associated Ag, CCR6, CD103, and IL-23R expressing epidermal CD8 T cells was highly enriched. Epidermal CD8 T cells expressing the T(RM) marker CD103 responded to ex vivo stimulation with IL-17A production and epidermal CD4 T cells responded with IL-22 production after as long as 6 y of TNF-α inhibition. Our data suggest that epidermal T(RM) cells are retained in resolved psoriasis and that these cells are capable of producing cytokines with a critical role in psoriasis pathogenesis. We provide a potential mechanism for a site-specific T cell–driven disease memory in psoriasis.